Spatial Determinants of CO2 Emissions on Java Island: STIRPAT Framework and SAR Model - Habibullah, M. Hafidz; Cotva, Bunga Musva; Putra, Hafidh Rean; Sari, Agustin Kurnia; Berliana, Sarni Maniar (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Java Island, Indonesia’s economic and population hub, faces intense environmental pressure from CO2 concentration, exhibiting strong spatial dependence across its 118 regencies and cities. This study examines the determinants of CO2 concentration and their spillover effects using an extended STIRPAT framework and a Spatial Autoregressive (SAR) model, applied to 2024 secondary data from BPS-Statistics Indonesia and Google Earth Engine (GEE). The SAR model outperforms OLS, with lower AIC (364.8979 vs. 489.0563) and BIC (387.0634 vs. 508.4551), confirming spatial effects. In SAR models, interpretation relies on decomposing estimated coefficients into direct effects (impacts within a region) and indirect or spillover effects (impacts transmitted to neighboring regions), allowing a more nuanced understanding of spatial influence. Population density and manufacturing sector GRDP increase emissions, while NDVI and HDI reduce them. Population density and manufacturing sector GRDP increase concentration, while NDVI and HDI reduce them. Notably, indirect (spillover) effects consistently surpass direct effects, driven by commuter flows in urban hubs like Jabodetabek and industrial pollution spillovers. These findings inform regional climate strategies, emphasizing cross-regency reforestation and emission controls to support Indonesia’s Enhanced Nationally Determined Contribution (ENDC) goals.